Once-weekly tirzepatide versus once-daily insulin degludec as add-on to metformin with or without SGLT2 inhibitors in patients with type 2 diabetes (SURPASS-3): a randomised, open-label, parallel-group, phase 3 trial - Ludvik, Bernhard; Giorgino, Francesco; Jódar, Esteban; Frias, Juan P; Fernández Landó, Laura; Brown, Katelyn; Bray, Ross; Rodríguez, Ángel (The Lancet (British edition), 2021)
Tirzepatide is a novel dual glucose-dependent insulinotropic polypeptide and GLP-1 receptor agonist under development for the treatment of type 2 diabetes. We aimed to assess the efficacy and safety of tirzepatide versus titrated insulin degludec in people with type 2 diabetes inadequately controlled by metformin with or without SGLT2 inhibitors. In this open-label, parallel-group, multicentre (122 sites), multinational (13 countries), phase 3 study, eligible participants (aged ≥18 years) had a baseline glycated haemoglobin (HbA1c) of 7·0–10·5%, body-mass index of at least 25 kg/m2, stable weight, and were insulin-naive and treated with metformin alone or in combination with an SGLT2 inhibitor for at least 3 months before screening. Participants were randomly assigned (1:1:1:1), using an interactive web-response system, to once-weekly subcutaneous injection of tirzepatide (5, 10, or 15 mg) or once-daily subcutaneous injection of titrated insulin degludec, and were stratified by country, HbA1c, and concomitant use of oral antihyperglycaemic medications. Tirzepatide was initially given at 2·5 mg and the dose was escalated by 2·5 mg every 4 weeks until the assigned dose was reached. Insulin degludec was initially given at 10 U per day and was titrated once weekly to a fasting self-monitored blood glucose of less than 5·0 mmol/L (<90 mg/dL), following a treat-to-target algorithm, for 52 weeks. The primary efficacy endpoint was non-inferiority of tirzepatide 10 mg or 15 mg, or both, versus insulin degludec in mean change from baseline in HbA1c at week 52. Key secondary efficacy endpoints were non-inferiority of tirzepatide 5 mg versus insulin degludec in mean change from baseline in HbA1c at week 52, superiority of all doses of tirzepatide versus insulin degludec in mean change from baseline in HbA1c and bodyweight, and the proportion of participants achieving HbA1c of less than 7·0% (<53 mmol/mol) at week 52. We used a boundary of 0·3% to establish non-inferiority in HbA1c difference between treatments. Efficacy and safety analyses were assessed in the modified intention-to-treat population (all participants who received at least one dose of study drug). This trial is registered with ClinicalTrials.gov, number NCT03882970, and is complete. Between April 1 and Nov 15, 2019, we assessed 1947 participants for eligibility, 1444 of whom were randomly assigned to treatment. The modified intention-to-treat population was 1437 participants from the tirzepatide 5 mg (n=358), tirzepatide 10 mg (n=360), tirzepatide 15 mg (n=359), and insulin degludec (n=360) groups. From a mean baseline HbA1c of 8·17% (SD 0·91), the reductions in HbA1c at week 52 were 1·93% (SE 0·05) for tirzepatide 5 mg, 2·20% (0·05) for tirzepatide 10 mg, and 2·37% (0·05) for tirzepatide 15 mg, and 1·34% (0·05) for insulin degludec. The non-inferiority margin of 0·3% was met. The estimated treatment difference (ETD) versus insulin degludec ranged from –0·59% to –1·04% for tirzepatide (p<0·0001 for all tirzepatide doses). The proportion of participants achieving a HbA1c of less than 7·0% (<53 mmol/mol) at week 52 was greater (p<0·0001) in all three tirzepatide groups (82%–93%) versus insulin degludec (61%). At week 52, from a baseline of 94·3 kg (SD 20·1), all three tirzepatide doses decreased bodyweight (–7·5 kg to –12·9 kg), whereas insulin degludec increased bodyweight by 2·3 kg. The ETD versus insulin degludec ranged from –9·8 kg to –15·2 kg for tirzepatide (p<0·0001 for all tirzepatide doses). The most common adverse events in tirzepatide-treated participants were mild to moderate gastrointestinal events that decreased over time. A higher incidence of nausea (12–24%), diarrhoea (15–17%), decreased appetite (6–12%), and vomiting (6–10%) was reported in participants treated with tirzepatide than in those treated with insulin degludec (2%, 4%, 1%, and 1%, respectively). Hypoglycaemia (<54 mg/dL or severe) was reported in five (1%), four (1%), and eight (2%) participants on tirzepatide 5, 10, and 15 mg, respectively, versus 26 (7%) on insulin degludec. Treatment discontinuation due to an adverse event was more common in the tirzepatide groups than in the insulin degludec group. Five participants died during the study; none of the deaths were considered by the investigators to be related to the study treatment. In patients with type 2 diabetes, tirzepatide (5, 10, and 15 mg) was superior to titrated insulin degludec, with greater reductions in HbA1c and bodyweight at week 52 and a lower risk of hypoglycaemia. Tirzepatide showed a similar safety profile to that of GLP-1 receptor agonists. Eli Lilly and Company.